3D Versus 4K Display System – Influence of "State-of-the-art"-Display Technique on Surgical Performance (IDOSP-study) in Minimally Invasive Surgery: A Randomized Cross-over Trial. Issue 5 (November 2020) - Wahba, Roger; Datta, Rabi; Bußhoff, Jana; Bruns, Thomas; Hedergott, Andrea; Gietzelt, Caroline; Dieplinger, Georg; Fuchs, Hans; Morgenstern, Bernd; Möller, Desdemona; Hellmich, Martin; Bruns, Christiane J.; et al.
Abstract : Objective: To evaluate if "state-of-the-art" 3D- versus 4K-display techniques could influence surgical performance. Background: High quality minimally invasive surgery is challenging. Therefore excellent vision is crucial. 3D display technique (3D) and 2D-4K technique (4K) are designed to facilitate surgical performance, either due to spatial resolution (3D) or due to very high resolution (4K). Methods: In randomized cross-over trial the surgical performance of medical students (MS), non-board certified surgeons (NBC), and board certified surgeons (BC) was compared using 3D versus 4K display technique at a minimally invasive training Parkour. Results: One hundred twenty-eight participants were included (February 2018 through October 2019, 49 MS, 39 NBC, 40 BC). The overall Parkour time (s) 3D versus 4K was 712.5 s ± 17.5 s versus 999.5 s ± 25.1 s ( P < 0.001) for all levels of experience. It was (3D vs 4K) for MS (30 tasks) 555.4 s ± 28.9 s versus 858.7 s ± 41.6 s, ( P < 0.0001), for NBC (42 tasks) 935.9 s ± 31.5 s versus 1274.1 s ± 45.1 s ( P =< 0.001) and for BC (42 task) 646.3 s ± 30.9 s versus 865.7 s ± 43.7 s ( P < 0.001). The overall number of mistakes was (3D vs 4K) 10.0 ± 0.5 versus 13.3 ± 0.7 ( P < 0.001), for MS 8.9 ± 0.9 versus 13.1 ± 1.1 ( P < 0.001), for NBC 12.45 ± 1.0 versus 16.7 ± 1.2 ( P < 0.001) and for BC 8.8 ± 1.0 versus 10.0 ± 1.2 ( P = 0.18). MS, BC, and NBC showed shorter performance time in 100% of the task with 3D (significantly in 6/7 tasks). For number of mistakes the effect was less pronounced for more experienced surgeons. The National Aeronautics and Space Administration-task load index was lower with 3D. Conclusion: 3D laparoscopic display technique optimizes surgical performance compared to the 4K technique. Surgeons benefit from the improved visualization regardless of their individual surgical expertise. Abstract : Supplemental Digital Content is available in the text